Violência doméstica: a realidade das mulheres que denunciam: Vitória (ES) 2004 - Vitória, Mariza Barros Ribeiro da (2010)
This objective work to evidence the changes or stays in the life of the women who had looked the Police station Specialized in Attendance to the Woman in the city of capital Victory of the state of the Espirito Santo in the year of 2004 to register that they had been victims of violence in the domestic space and that they kept an affective relationship with the aggressor in married life’s relation. By means of the use of interviews with the denouncers the research searched to analyze and to after understand histories and the trajectories of life of the victims the denunciation and, with this, to remember the paper of the public politics in the process of confronting of the violence against the woman . The conclusion of this work sends the perception of that even so they were not imbued of a feeling to get influenced by the movement feminist or another politician-ideological chain, the studied women had found alternatives proper to face its realities. Some had obtained to modify its lives others had been obliged to accept the staying of the oppression picture, therefore to survive in some occasions means to fight with weapons that if making use.